TECHNOLOGY OF RESTORATION OF ROLLED MANDREL OF CONTINUOUS MILL PQF IN TUBE-SHOP OF OAO «BMZ» – MANAGEMENT COMPANY OF HOLDING «BMK» - A. G. Shcheglov (Литьë и металлургия)
The technology of chrome plating on the mandrel of continuous rolling mill, used in tube-rolling shop of «Byelorussian Steel Works» was shown. Development of technology enabled to reduce considerably funds for their purchase.